Prolonged Life and Fast Secondary Formation of the Electrodes of Lead-Acid Battery during Charge-Discharge Cycle under High-Pressure Crystallization. Issue 1 (1st January 2015) - Maeda, Kouji; Arakawa, Naoko; Matsuda, Satoshi; Fukui, Keisuke; Kuramochi, Hidetoshi
Abstract : To make larger capacity of charge–discharge of lead-acid batteries at high pressure after the initial formation of Plante-type electrodes, we studied the effect of high pressure on prolonged life testing. Electrode life was evaluated by determining the time of detachment of active crystals (Pb, PbOx and PbSO4 ) or the drop in ampere-hour efficiency during the charge–discharge cycle. Prolonged life testing, active crystals (Pb, PbOx and PbSO4 ) on the electrodes used in charge–discharge cycles at atmospheric pressure were easily detached when the electric current was increased to 2.7 mA/cm 2, but the electrodes used at 100 MPa remained very tough until 8.0 mA/cm 2 was reached. To increase the electric capacity of electrodes (i.e. in the second formation process), long-term charge–discharge was performed at a high electric current (5.3 mA/cm 2 ). Faster second formation of electrodes at this high current was impossible at a charge of 3.6 As under atmospheric pressure, but it was possible at 6 As and 100 MPa.